JUNIOR SCHOOL STUDENTS NEED OF LEARNING SOURCE IN FORM OF MOBILE LEARNING ENCYCLOPEDIA - Siska Ferastia; Nurkhairo Hidayati (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Natural Science subject is a science that examines events that occur in nature with scientific activities. One of the scientific activities that can be carried out is practical experiment. Students are required to be able to use various kinds of laboratory tools in order to avoid mistakes in the experimental result. Therefore, it is necessary to develop learning resources that introduce biology laboratory tools. One of the learning resources that can be used is the encyclopedia. This study aims to analyze the problem faced by teachers and students in the implementation of Science-Biology learning, as well as, analyze need of students for learning resource that will be used to introduce biology laboratory tools. This study using a survey method using a questionnaire as a data collection. The instrument is interview sheet, problem analysis questionnaire, and product needs questionnaire. The data were analyzed using quantitative descriptive techniques. The results showed 73% of students did not know the name, function and how to use biology laboratory equipment, and as many 86% of students need learning resources that were useful for introducing biology laboratory tool and material.